Existence of an inactive pool of acetylcholinesterase in chicken brain. - Chatel, J M (1993)
We analyzed acetylcholinesterase (AcChoEase; EC 3.1.1.7) activity and AcChoEase immunoreactive protein in chicken brain by using five monoclonal antibodies raised against chicken AcChoEase. Four of them specifically recognized AcChoEase catalytic subunits in Western blots and one, C-131, recognized only enzymatically active AcChoEase. We observed considerable differences in the ratio of immunoreactive protein to catalytic activity in various fractions, indicating the existence of inactive AcChoEase protein. This inactive AcChoEase component was more abundant in a low-salt-soluble extract than in a subsequent detergent-soluble extract. On the basis of the ratio between activity and immunoreactivity, we calculated that the inactive component represents about 30% of the total AcChoEase subunits in chicken brain. The immunoreactive AcChoEase protein sedimented in sucrose gradients like the active molecular forms; the G1 and G2 peaks contained inactive molecules, whereas the G4 peak appeared to contain only active AcChoEase. The bulk of inactive AcChoEase reacted with the organophosphate cholinesterase inhibitor O-ethyl S-[2-(diisopropylamino)ethyl]methylphosphonothioate (MTP) but was found to bind the active site affinity ligand N-methylacridinium poorly and was not recognized by the active-form-specific monoclonal antibody, C-131. In addition, most of this fraction is sensitive to endoglycosidase H and binds the lectin wheat germ agglutinin poorly, suggesting that it was not processed in the Golgi apparatus. From these observations, we propose that the active and inactive AcChoEase components are differently folded.